2011
DOI: 10.1007/s12311-011-0248-3
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Review: Synaptic Integration in the Cerebellar Nuclei—Perspectives From Dynamic Clamp and Computer Simulation Studies

Abstract: The cerebellar nuclei (CN) process inhibition from Purkinje cells (PC) and excitation from mossy and climbing fiber collaterals. CN neurons in slices show intrinsic pacemaking activity, which is easily modulated by synaptic inputs. Our work using dynamic clamping and computer modeling shows that synchronicity between PC inputs is an important factor in determining spike rate and spike timing of CN neurons and that brief pauses in PC inputs provide a potent stimulus to trigger CN spikes. Excitatory input can eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…Smaller neurons have a lower capacitance with a broader action potential, a strong late component after-hyperpolarization and longer rebound (for review see [17]). Our whole-cell in vivo recordings of post-hoc morphologically identified cells under anesthesia support these trends and will allow modelers of the CN to further expand and fine-tune the computational repertoire of CNNs in intact animals [63,78,79]. …”
Section: Discussionmentioning
confidence: 76%
“…Smaller neurons have a lower capacitance with a broader action potential, a strong late component after-hyperpolarization and longer rebound (for review see [17]). Our whole-cell in vivo recordings of post-hoc morphologically identified cells under anesthesia support these trends and will allow modelers of the CN to further expand and fine-tune the computational repertoire of CNNs in intact animals [63,78,79]. …”
Section: Discussionmentioning
confidence: 76%
“…Realistic modeling of cerebellar cells has been taking place for decades, and there are several models that could be used for this endeavor (e.g. [25, 38, 65, 66]). These models can point out possible necessary conditions for the granule layer inputs, Purkinje cells, and molecular layer interneurons in order to express stochastic synchronization.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that a model encompassing bidirectional plasticity at the GC-PC synapse supervised by CFs6, PC inhibition by molecular layer interneurons (MLIs)78 as well as plasticity at the mossy fiber (MF) to medial vestibular nuclei (MVN) synapse910 (Fig. 1a) can reliably reproduce empirical data of the vestibulo-ocular reflex (VOR) phase-reversal task.…”
mentioning
confidence: 99%